2021
DOI: 10.48550/arxiv.2101.07617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feynman Integral in Quantum Walk, Barrier-top Scattering and Hadamard Walk

Kenta Higuchi

Abstract: The aim of this article is to relate the discrete quantum walk on Z with the continuous Schrödinger operator on R in the scattering problem. Each point of Z is associated with a barrier of the potential, and the coin operator of the quantum walk is determined by the transfer matrix between bases of WKB solutions on the classically allowed regions of both sides of the barrier. This correspondence enables us to represent each entry of the scattering matrix of the Schrödinger operator as a countable sum of probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There is no doubt that studies on scattering theory is one of the interesting topic of the Schrödinger equation. Recently, it is revealed that the scatterings of some fundamental stationary Schrödinger equations on the real line with not only delta potentials [26,7,18] but also continuous potential [6] can be recovered by discrete-time quantum walks. These induced quantum walks are given by the following setting: the non-trivial quantum coins are assigned to some vertices in a finite region on the one-dimensional lattice as the impurities and the freequantum coins are assigned at the other vertices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that studies on scattering theory is one of the interesting topic of the Schrödinger equation. Recently, it is revealed that the scatterings of some fundamental stationary Schrödinger equations on the real line with not only delta potentials [26,7,18] but also continuous potential [6] can be recovered by discrete-time quantum walks. These induced quantum walks are given by the following setting: the non-trivial quantum coins are assigned to some vertices in a finite region on the one-dimensional lattice as the impurities and the freequantum coins are assigned at the other vertices.…”
Section: Introductionmentioning
confidence: 99%
“…The initial state is given so that quantum walkers inflows into the perturbed region at every time step. It is shown that the scattering matrix of the quantum walk on the one-dimensional lattice can be explicitly described by using a path counting in [11] and this path counting method can be described by a discrete analogue of the Feynmann path integral [6]. There are some studies for the scattering theory of quantum walks under slightly general settings and related topics [25,23,24,20,21,27,12].…”
Section: Introductionmentioning
confidence: 99%